Comparison of Two Cuff Inflation Protocols to Measure Arterial Occlusion Pressure in Males and Females - Pat R. Vehrs; Chase Blazzard; Hannah C. Hart; Nicole Kasper; Ryan Lacey; Daniela Lopez; Shay Richards; Dennis L. Eggett (Applied Sciences, 2023)
We measured the arterial occlusion pressure (AOP) in the dominant (DOM) and non-dominant (NDOM) legs of males (n = 20) and females (n = 20), 19–26 years of age, using a continuous (CONT) and incremental (INCR) cuff inflation protocol. ANOVA revealed no significant differences in AOP within (<1 mmHg; p > 0.493) or between (<6 mmHg; p > 0.418) the DOM and NDOM legs in males or females with either CONT or INCR. There were no significant sex differences in AOP in the DOM or NDOM legs when using CONT (<3 mmHg; p > 0.838) or INCR (<3 mmHg; p > 0.856). Measures of AOP are highly reliable, as evidenced by correlation coefficients >0.96 and small mean differences (<1.5 mmHg) between repeated measures. The choice of which cuff inflation protocol to use is one of personal preference. The AOP is not always greater in the dominant or larger leg. Although mean differences in AOP between the two legs was small, actual differences of over 100 mmHg could lead to unsafe and ineffective cuff inflation pressures during BFR if AOP is measured in only one leg. Further investigation of factors that explain difference in AOP between legs and between males and females is warranted. To ensure safe and effective use of BFR during exercise, AOP of both limbs should be measured regularly.